Analisis Sistem Rantai Pasok Baja - Syaikhuna Ibnu Jarir; Dwi Kartika Wulandari; Desma Ulfitriani; Hendra Gunawan; Jeni Rolika (Jurnal Optimasi Sistem Industri, 2012)
PT Karakatau Steel is the which manufacture iron steel factory in Cilegon, Banten, Indonesia. That said Pujawan supply chain is the network of the which companies are working to create and deliver togerther the product into end customer. Production activity in PT Krakatau Steel include raw steel, producing and selling work-in-process steel, finished steel products and steel billet Including, HRC and CRC, steel wire bar, and also steel-concrete, profile steel, and steel pipe.In finished steel products, steel production company Could match with specification and customer needs. PT Karaktau steel sales have activity in the domestic market and export market by using porduction system make-to-stock. To control product quality of product produced, well relatioionship keep company with raw material suppliers, and also the make an impact on production controling cost.Supplier selection procedure uses the tender mechanism, chosen supplier is the best supplier That consistency ratio have high level of priority and wight . Company built product storage in easy access places to maintain product delivery Fluency by choosing train as land transportation unit and ship as sea transport unit.